2017
DOI: 10.1080/07357907.2016.1272695
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Sphingosine-1-Phosphate Metabolizing Enzymes in Oral Cancer Correlate With Clinicopathological Attributes

Abstract: We have determined the gene expression of sphingosine-1-phosphate (S1P) metabolizing enzymes (SphK1, SphK2, SGPL1, SGPP1, SGPP2, PPAP2A, PPAP2B, and PPAP2C) by quantitative real-time polymerase chain reaction in tumor tissues and adjacent normal tissues of 50 oral squamous cell carcinoma (OSCC) patients. Expression of SphK1 and SGPP1 genes was up-regulated significantly in 70% and 75% OSCC tumors respectively. Importantly, expression of SphK2 and PPAP2B was down-regulated in the tumor tissues of 70% OSCC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
5
21
0
Order By: Relevance
“…Recently (Vishwakarma et al . ) also showed that in patients with oral squamous cell carcinoma, the S1P phosphatases and sphingosine kinases were differentially regulated in tumors and tumor metastasis. There are conflicting reports on the role of SphK1 in inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…Recently (Vishwakarma et al . ) also showed that in patients with oral squamous cell carcinoma, the S1P phosphatases and sphingosine kinases were differentially regulated in tumors and tumor metastasis. There are conflicting reports on the role of SphK1 in inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…Flanagan et al reported that downregulating PLPP2 transcriptionally repressed by p53 impaired anchorage-dependent growth of cancer cell lines MCF7, SK-LMS1, MG63, and U2OS, as well as decreased cell proliferation by delaying entry into the S phase of the cell cycle [18]. In addition, it has been demonstrated that PLPP3 was downregulated in approximately 70% of oral squamous cell carcinoma (OSCC) patients, and low expression of PLPP3 positively correlated with TNM stage in OSCC patients [7]. These studies indicated that although belonging to a phosphatidate phosphatase family, different members of the PLPP family function as an oncogene or tumor suppressor in different tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, through analyzing a comparative genomic hybridization array and expression profiling data for a series of 152 ductal breast cancer tissues and 21 breast cancer cell lines, Bernard-Pierrot and colleagues reported that PLPP5 was overexpressed, which contributed to cell survival and cell transformation. Importantly, the oncogenic properties of PLPP5 were further demonstrated by its ability to transform NIH-3 T3 fibroblasts, further inducing their anchorage-independent growth [6]; in oral squamous cell carcinoma (OSCC) patients, PLPP3 was downregulated in approximately 70% OSCC patients and PLPP3 expression negatively correlated with TNM stage and tumor volume [7]. Moreover, Mahmood et al reported that overexpression of PLPP5 caused by amplification of the 8p11-12 chromosomal region, a common genetic event in many epithelial cancers, was found in several cancers, including breast cancer, pancreatic adenocarcinomas and lung carcinoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of SPL expression has also been reported in prostate cancer and oral squamous cell carcinoma (OSCC) [ 74 , 76 ]. In contrast, upregulation of SGPL1 mRNA has been reported in OSCC, hepatocellular carcinoma, and ovarian cancer [ 77 79 ]. The etiology of this finding and its impact on carcinogenesis remain to be clarified.…”
Section: Structure and Functions Of Splmentioning
confidence: 99%